Secure Logging as a Service –Proactive Attribute Based Encryption-A Survey - Dr. Vijay Bhardwaj (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Confidentiality ensures that the information is not shared with anybody who isn't supposed to know. It also ensures that the information is kept private. Integrity ensures that only authorised users have access to information. Availability ensures that systems respond quickly and that unauthorised users are not denied access to services. Maintaining log records for an organisation is critical for detecting and troubleshooting any harmful behaviour, such as data modification, deletion, and so on, that has happened within the business. Proper encryption is used to ensure the security, integrity, and privacy of log records, and encrypted data is stored in the cloud to save money on storage. This study examines alternative techniques for preserving log record secrecy, as well as the factors connected with log records such as accuracy, verifiability, confidentiality, and tamper resistance.